2022
DOI: 10.3390/polym14204446
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nanohydroxyapatite/Pectin Composite from Opuntia Ficus-Indica Cladodes for the Management of Microbial Infections

Abstract: Hydroxyapatite (HAp) attracts interest as a biomaterial for use in bone substitution or allografts. In the current work, biomaterial nanocomposites based on HAp and pectin were synthesized by using the double decomposition method, which involved using pectin extracted from fresh cladodes of the prickly pear, Opuntia ficus-indica. The crystallinity, purity, and several analytical techniques like Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy were used to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this sense, some of this research is reported here, emphasizing the synthesis and surface characteristics, such as the size and distribution of the particles, and the functional groups of the composite systems in focus: alginate@ HAp, 103−107 chitosan@HAp, 115−117 and pectin@HAp. 118 Therefore, the use of various natural and synthetic polymers as templates for the growth of HAp allowed the production of materials that will serve as a support for osteogenic activity. In this way, HAp and bioactive molecules, such as polysaccharides and proteins, are possible in the preparation of biomaterials, as these bioactive molecules will function as an organic template during the preparation of these different structures that help in the repair and construction of bone tissue.…”
Section: Biomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, some of this research is reported here, emphasizing the synthesis and surface characteristics, such as the size and distribution of the particles, and the functional groups of the composite systems in focus: alginate@ HAp, 103−107 chitosan@HAp, 115−117 and pectin@HAp. 118 Therefore, the use of various natural and synthetic polymers as templates for the growth of HAp allowed the production of materials that will serve as a support for osteogenic activity. In this way, HAp and bioactive molecules, such as polysaccharides and proteins, are possible in the preparation of biomaterials, as these bioactive molecules will function as an organic template during the preparation of these different structures that help in the repair and construction of bone tissue.…”
Section: Biomaterialsmentioning
confidence: 99%
“…Over the years, different routes for obtaining of nanostructured polysaccharide@HAp systems have been developed to achieve specific properties and characteristics for different applications. In this sense, some of this research is reported here, emphasizing the synthesis and surface characteristics, such as the size and distribution of the particles, and the functional groups of the composite systems in focus: alginate@HAp, chitosan@HAp, and pectin@HAp …”
Section: Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strategies used to enhance its mechanical properties is the addition of nanoparticles or small organic molecules to the pectin matrix. In this way, while the mechanical properties of the pectin matrix become resistant against forces, drug release behaviors, antimicrobial activity, and bioactive ability also improved, i.e., two birds with one stone.…”
Section: Introductionmentioning
confidence: 99%
“…°ranging between (− 19.271 𝐾𝐽/𝑚𝑜𝑙) and (− 22.093 𝐾𝐽/𝑚𝑜𝑙) indicate that the adsorption process occurred spontaneously. In general, it has already been found that values of ∆Gads equal to -20 kJ/mol are compatible with physical adsorption or those up to -40 kJ/mol or above with chemical adsorption[26] …”
mentioning
confidence: 98%